2018
DOI: 10.1097/wno.0000000000000572
|View full text |Cite
|
Sign up to set email alerts
|

Visual Structure and Function in Collision Sport Athletes

Abstract: This study showed that retinal axonal and neuronal loss is present among collision sport athletes, with most notable differences seen in boxers. These findings are accompanied by reductions in visual function and QOL, similar to patterns observed in multiple sclerosis, Alzheimer and Parkinson diseases. Vision-based changes associated with head trauma exposure that have the potential to be detected in vivo represent a unique opportunity for further study to determine if these changes in collision sport athletes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 18 publications
1
24
2
Order By: Relevance
“…The literature has shown that decreased RNFL thickness correlates with visual outcomes, particularly reduced low contrast letter acuity . In this study, there were no significant visual outcomes observed and RNFL thinning was not shown to correlate with reduced visual acuity.…”
Section: Discussioncontrasting
confidence: 70%
See 4 more Smart Citations
“…The literature has shown that decreased RNFL thickness correlates with visual outcomes, particularly reduced low contrast letter acuity . In this study, there were no significant visual outcomes observed and RNFL thinning was not shown to correlate with reduced visual acuity.…”
Section: Discussioncontrasting
confidence: 70%
“…The literature has shown that decreased RNFL thickness correlates with visual outcomes, particularly reduced low contrast letter acuity. 26,43 In this study, there were no significant visual outcomes observed and RNFL thinning was not shown to correlate with reduced visual acuity. The findings of normal cognition and mood within this study cohort underlines the need to perform similar studies in those exhibiting clinical features.…”
Section: Discussioncontrasting
confidence: 51%
See 3 more Smart Citations